Diver-generated photomosaics as a tool for monitoring temperate rocky reef ecosystems - Spyksma, Arie J. P.; Miller, Kelsey I.; Shears, Nick T. (Frontiers in Marine Science, 2022)
Robust monitoring data provides important information on ecosystem responses to anthropogenic stressors; however, traditional monitoring methodologies, which rely heavily on time in the field, are resource intensive. Consequently, trade-offs between data metrics captured and overall spatial and temporal coverage are necessary to fit within realistic monitoring budgets and timeframes. Recent advances in remote sensing technology have reduced the severity of these trade-offs by providing cost-effective, high-quality data at greatly increased temporal and spatial scales. Structure-from-motion (SfM) photogrammetry, a form of remote sensing utilising numerous overlapping images, is well established in terrestrial applications and can be a key tool for monitoring changes in marine benthic ecosystems, which are particularly vulnerable to anthropogenic stressors. Diver-generated photomosaics, an output of SfM photogrammetry, are increasingly being used as a benthic monitoring tool in clear tropical waters, but their utility within temperate rocky reef ecosystems has received less attention. Here we compared benthic monitoring data collected from virtual quadrats placed on photomosaics with traditional diver-based field quadrats to understand the strengths and weaknesses of using photomosaics for monitoring temperate rocky reef ecosystems. In north-eastern New Zealand, we evaluated these methods at three sites where sea urchin barrens were prevalent. We found key metrics (sea urchin densities, macroalgae canopy cover and benthic community cover) were similar between the two methods, but data collected via photogrammetry were quicker, requiring significantly less field time and resources, and allowed greater spatial coverage than diver-based field quadrats. However, the use of photomosaics was limited by high macroalgal canopy cover, shallow water and rough sea state which reduced stitching success and obscured substratum and understory species. The results demonstrate that photomosaics can be used as a resource efficient and robust method for effectively assessing and monitoring key metrics on temperate rocky reef ecosystems.